Thermal-hydraulic stability investigations of once through helically coiled steam generators for SMR applications - Magni, María Celeste; Marcel, Christian Pablo; Delmastro, Dario Fabian (Elsevier Science SA, 2022)
Fil: Magni, María Celeste. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina